WAREHOUSHING AND INVENTORY INFORMATION SYSTEM MODEL USING RADIO FREQUENCY IDENTIFICATION (RFID) IN EASTERN NAVAL WAREHOUSING - Indra Agustian; Eka Muktiono; Akhmat Nuryadin; Bambang Suharjo (JOURNAL ASRO, 2019)
Eastern Naval Warehousing is the technical implementation elements in charge of receiving, storing, maintaining and distributing supplies to support existing user in the Navy in particular user located in the eastern region. To support the operational activities of the Navy, Eastern Naval Warehousing as service organizations should be supported with the provision of an information system capable of supporting the activities become more optimal provisioning. Speed and accuracy of support provision to user is an indication for the success of a service. Information technology nowadays has grown very rapidly to develop into the current warehousing system. RFID (Radio Frequency Identification) is the process of identifying an object automatically by Radio Frequency. There are two important components of an RFID system is the card (tag) and the reader. Application warehousing information system can be integrated with RFID technology, so that the system can run more optimal for warehousing system. This research aims to design warehousing information system based on RFID in Eastern Naval Warehousing used in processing existing warehousing system to gain optimal in provisioning operations running in Eastern Naval Warehousing to support provisioning activities to meet the requirement of existing user in Navy. Field studies conducted in Eastern Naval Warehousing, aimed to determine the current state of warehousing system that runs to identify existing problems. Furthermore, to process the data, created the design of an information system based on RFID warehousing in software system. This paper get to report out of the goods, report the amount of inventory in real time, the location of goods and EOQ value of goods to determine the optimal inventory level of each item.